Up‐regulation of HOXA‐AS2 and MEG3 long non‐coding RNAs acts as a potential peripheral biomarker for bipolar disorder - Hosseini, Maryam; Mokhtari, Mohammad Javad (Journal of cellular and molecular medicine, 2024)
Bipolar disorder (BD) is a psychiatric condition that is frequently misdiagnosed and linked to inadequate treatment. Long non‐coding RNAs (lncRNAs) have lately gained recognition as crucial genetic elements and are now regarded as regulatory mechanisms in the neurological system. Our objective was to measure the quantities of HOXA‐AS2 and MEG3 ncRNA transcripts. HOXA‐AS2 and MEG3 ncRNA levels were checked in the peripheral blood of 50 type I BD and 50 control samples by real‐time PCR. Furthermore, we conducted ROC curve analysis and correlation analysis to examine the association between gene expression and specific clinical characteristics in instances with BD. Additionally, a computational study was performed to investigate the binding sites of miRNAs on the HOXA‐AS2 and MEG3 lncRNAs. BD subjects showed a significant increase in the expression of HOXA‐AS2 and MEG3 compared to controls. The lncRNAs HOXA‐AS2 and MEG3 have an area under the ROC curve (AUC) values of 0.70 and 0.71, respectively. There was a significant correlation between the expression levels of ncRNAs HOXA‐AS2 and MEG3 in the peripheral blood of patients with BD and occupation scores. The data presented indicate a potential correlation between the expression of HOXA‐AS2 and MEG3 lncRNAs with an elevated risk of BD. Furthermore, these lncRNAs may be linked to several molecular pathways. Our findings indicate that the amounts of lncRNAs HOXA‐AS2 and MEG3 in transcripts might be a promising potential biomarker for patients with BD.